Supporting packet-data QoS in next generation cellular networks. - Koodli, R. (IEEE Communications magazine)
In the past few years, the Internet has grown beyond anyone's reasonable imagination into a universal communication platform. At the same time the cellular networks, with their ability to reach a person ?anywhere, anytime,? have grown impressively as well. Thus the combination of mobile networks and the Internet into the so called ?mobile Internet? promises to be an important technology area. The indications are clear: the cellular networks are rapidly adopting suitable network models for supporting packet data services. A key component of this packet data service model is quality of service (QoS), which is crucial for supporting disparate services envisioned in the future cellular networks. We describe the packet data QoS architecture and specific mechanisms that are being defined for multi-service QoS provisioning in the Universal Mobile Telecommunication Systems